#### Answer

$\sqrt 13$

#### Work Step by Step

$a = 1, b=-3, c=-1$
$\sqrt {b^2-4ac}$
=$ \sqrt {(-3)^2 - (4\times1\times-1)}$
=$\sqrt {9-(-4)}$
=$\sqrt {9+4}$
=$\sqrt 13$
=$\sqrt 13$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\sqrt 13$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.